Minimal immunological effects on workers with prolonged low exposure to inorganic mercury. Issue 6 (June 1997) - Soleo, L; Vacca, A; Vimercati, L; Bruno, S; Di Loreto, M; Zocchetti, C; Di Stefano, R; Candilio, G; Lasorsa, G; Franco, G; Foa, V
Abstract : OBJECTIVES: This study was carried out to investigate possible immunological changes in workers with prolonged low exposure to inorganic mercury in a fluorescent light bulb factory. METHODS: 29 immunological variables were examined in 34 workers with prolonged low level exposure to inorganic mercury (exposed workers) and 35 unexposed workers as the controls. The selected indicator of mercury exposure was concentration of mercury in the urine (U-Hg), which declined progressively from 36.0 micrograms/l in 1978 to 6.0 micrograms/l in the study year 1994. RESULTS: None of the exposed workers had ever shown signs of either acute or chronic inorganic mercury toxicity or had shown any form of hypersensitivity. The only changes found in the exposed workers, compared with the controls, were a reduction of the cells that express cluster differentiation (CD25, (T activation antigen (Tac antigen))) and concentrations of tumour necrosis factor-alpha (TNF-alpha) in serum. However, the decrease of cells that express CD25 was unrelated to occupational exposure and was, in all likelihood a chance finding. Conversely, the decline in serum TNF-alpha was closely associated with occupational exposure. However, no dose-response relation was found between U-Hg and TNF-alpha concentrations; nor were TNF-alpha concentrations affected by cumulative occupational exposure to inorganic mercury in over 20 years. CONCLUSIONS: Tentatively, we suggest that reduced serum TNF-alpha concentrations might be indicative of an in vivo functional defect of the monocyte macrophage system in this particular group of workers even though they were clinically asymptomatic.